Reflexões em torno de um conceito psicolingüístico de tipo de texto - Bonini, Adair (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The text type concept, after a phase in which it was focused on a cognitive view by van Dijk, based on the cognitive schemata theory of Rumelhart, became an object of study by other researchers (Adam, Swales) in new perspectives. These recent studies strengthened the debate, providing theoretical material for the re-discussion of the concept of type in psycholinguistic terms. Using a methodology of bibliographic research, the present article proposes to retake a discussion about textual superstructure.